CLINICAL-MORPHOLOGICAL FEATURES OF LIVER CHANGES IN CHILDREN WITH MONO- AND MIXED-ASSOCIATED TYPES OF INFECTIOUS MONONUCLEOSIS - Nezgoda, I.I.; Havryliuk, A.O.; Onofriichuk, O.S.; Demchyshyn, Y.M.; Haborets, Y.V.; Rosha, L.G.; Poprotska, S.M. (World of Medicine and Biology, 2021)
This article considers the clinical features of course of mono- and mixed-associated infectious mononucleosis in 60 patients with and without liver lesions. It was established that symptoms duration of infectious mononucleosis in patients with mixed-associated type were significant longer compared to mono-variant. The similar significant deviation was detected in laboratory tests in patients with mixed-associated infectious mononucleosis. The tendency to detection morphometric and echoacoustic changes of the liver, using ultrasound technique, was noted in the same group of patients. Were established clinical independent predictors of liver lesions in patients with infectious mononucleosis as: concomitant anemia, female sex, age>10 years. During scientific studies morphological changes of the liver in patient with infectious mononucleosis were described with typical signs such as: moderate lymphohistiocytic infiltration, hepatocyte protein dystrophy, moderate manifestations of coagulation necrosis of centrilobular hepatocytes, endothelial desquamation and moderate manifestations of intraductal cholestasis. The presence of EBV-virus was confirmed by immunohistochemistry essay.